Anterior Cervical Discectomy and Fusion Surgery: Results with Zero - Profile Spacer/Cage - Amir, Sohail; Nasir, Muhammad; Bibi, Zainab; Zahid, Pir Muhammad; Ahmad, Fayyaz; Khan, Imran; Tufail, Pir (Journal of Gandhara Medical and Dental Science, 2024)
OBJECTIVES This study aimed to evaluate the clinical outcomes of Anterior Cervical Discectomy and Fusion (ACDF) treatments for cervical disc degenerative disease (CDDD) using a Zero Profile cage. METHODOLOGY A retrospective study of 26 patients with cervical disc disease treated with a zero-profile cage was designed and followed up for an average of 12 months in descriptive research. For arm and neck pain, the Neck Disability Index (NDI) and Visual Analogue Scale (VAS) scores were used to assess function. Nurick’s myelopathy classification scheme based on gait impairments was also documented. RESULTS The average age of the 26 patients was 48.96 13.13 years (mean SD), with 44 percent falling into the 40-60-year age bracket. The male/female gender distribution was 21 (84%) and 04 (16%) male/female. Radiculomyelopathic symptoms were detected in 11 (28%) of the patients, with radicular pain occurring bilaterally in seven (28%) of the patients and on the left side in four (16%). A radiological examination of fusion was performed at six months and one year. The fusion had a success rate of 95 percent at six months (19 patients) and 100 percent at one year. CONCLUSION A zero-profile device provides biomechanical stability and fusion rates with excellent outcomes for one- and two-level ACDFs. Advantages include low rates of dysphagia, decreased operative time, restoration of cervical lordosis and disc height, and lack of cage subsidence or screw back out.